Infiltration into frozen soil: From core‐scale dynamics to hillslope‐scale connectivity. Issue 1 (17th December 2017) - Appels, Willemijn M.; Coles, Anna E.; McDonnell, Jeffrey J.
Abstract: Infiltration into frozen soil is a key hydrological process in cold regions. Although the mechanisms behind point‐scale infiltration into frozen soil are relatively well understood, questions remain about upscaling point‐scale results to estimate hillslope‐scale run‐off generation. Here, we tackle this question by combining laboratory, field, and modelling experiments. Six large (0.30‐m diameter by 0.35‐m deep) soil cores were extracted from an experimental hillslope on the Canadian Prairies. In the laboratory, we measured run‐off and infiltration rates of the cores for two antecedent moisture conditions under snowmelt rates and diurnal freeze–thaw conditions observed on the same hillslope. We combined the infiltration data with spatially variable data from the hillslope, to parameterise a surface run‐off redistribution model. We used the model to determine how spatial patterns of soil water content, snowpack water equivalent (SWE), and snowmelt rates affect the spatial variability of infiltration and hydrological connectivity over frozen soil. Our experiments showed that antecedent moisture conditions of the frozen soil affected infiltration rates by limiting the initial soil storage capacity and infiltration front penetration depth. However, shallow depths of infiltration and refreezing created saturated conditions at the surface for dry and wet antecedent conditions, resulting in similar final infiltration rates (0.3 mm hr −1 ). On the hillslope‐scale, the spatial variability of snowmelt rates controlled the development of hydrological connectivity during the 2014 spring melt, whereas SWE and antecedent soil moisture were unimportant. Geostatistical analysis showed that this was because SWE variability and antecedent moisture variability occurred at distances shorter than that of topographic variability, whereas melt variability occurred at distances longer than that of topographic variability. The importance of spatial controls will shift for differing locations and winter conditions. Overall, our results suggest that run‐off connectivity is determined by (a) a pre‐fill phase, during which a thin surface soil layer wets up, refreezes, and saturates, before infiltration excess run‐off is generated and (b) a subsequent fill‐and‐spill phase on the surface that drives hillslope‐scale run‐off.